Spanish After Service-Learning: A Comparative Study - Kanost, Laura (My University, 2017)
To begin to assess the impact of service-learning participation on subsequent use of Spanish, this study compares survey responses of students who completed conventional and servicelearning sections of the same intermediate university Spanish conversation course. Their responses suggest that the students who experienced service-learning generally describe themselves as more confident language users who continue their studies and use Spanish in their everyday lives at higher rates. In contrast, students who had completed the conventional sections tended to focus more on information learned and a greater percentage of them reported going on to study abroad.
Citation: “Spanish after service-learning: A comparative study”. Journal of Service-Learning in Higher Education 3 (2014). http://journals.sfu.ca/jslhe/index.php/jslhe/article/view/63/20